ANALISIS AKULTURASI BUDAYA JAWA – TIONGHOA DALAM CERITA RAKYAT KYAI TELINGSING - Ulya, Lisa Hilmayatul; Muhammad Noor Alfiandi; Mohammad Kanzunnudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study analyzes the forms of Javanese–Chinese cultural acculturation in the folklore Kyai Telingsing, widely known in Kudus Regency. Cultural acculturation is a blending process of two or more cultures without eliminating their original identity. Folklore plays an important role in shaping moral values, local wisdom, and character education for elementary school students. A qualitative approach with document analysis was used in this study. Data analysis followed Miles & Huberman’s model, including data reduction, data display, and conclusion drawing. The findings show that Kyai Telingsing contains cultural acculturation elements in religious, artistic, social, and traditional aspects. These values can serve as learning resources in elementary Bahasa Indonesia instruction. This study contributes to strengthening cultural literacy and encourages the use of local folklore as teaching material.